Narrativas en Torno a Las Relaciones Parentales de un Grupo De Adolescentes Que Prestan Servicio Militar y Pertenecen a Familias Monoparentales (2014)
In this research, the narratives of a group of teenagers who belong to single-parent families and serving in the military regarding parental relationships that circulate within the family dynamics were investigated. The parental relationship is the core of this research, the fact that the interaction of parents with their children, depends on the type, quality and quantity of the dual interaction between them. The research is based on the systems approach and that man is the object of knowledge to be the main part of an addition to considering the family changes are only possible if the interactions between its component system are modified, taking into account communication, hierarchy and parenting styles circulating in this